Komunikasi Interpersonal Relawan Pajak Dan Wajib Pajak Orang Pribadi Melayani Pelaporan SPT Via E-Filing - Latifah Aisah; Anita Kartika Sari (Universitas Linggabuana PGRI Sukabumi, 2022)
The directorate general of taxes refers to no. Per 12/ pj /2021, tax volunteers were individuals who sincerely assisted in tax activities and assessments about taxation. The purpose of this research is to find interpersonal communications by tax and tax volunteers while serving reporting as annual wpop via e-filling. Qualitative research methods are applied to the research, using the phenomenon approach to refer to a reporting process such as the annual wpop/employee. Data retrieval in this study involves observation and interviews. Research, to use e-filling a taxpayer must be completed in the reporting process such as the principal tax number, no efin, id, kk, and cut evidence. Interpersonal theory that makes it easier to communicate information with the person directly applied by the tax and taxpayers during such a reporting process.